Review on produccion processes and mechanical properties of dual phase austempered ductile iron - Basso, Alejandro Daniel (2012)
During the last few years, researchers have sought new ductile iron (DI) applications focusing on the development of mixed microstructures, such as ferritic-bainitic or ferritic-martensitic. These kinds of structures result in DI with a good combination of mechanical properties, compared to other conventional DI. The combination of properties offered by the mixed structure DI, particularly in “dual phase austempered ductile iron” (ADI) has opened new horizons for cast iron to replace steel castings and forgings in many engineering applications. This new DI has a particular microstructure composed of different amounts and morphologies of ausferrite and free ferrite. Dual phase ADI microstructures have afforded more opportunities for DI applications, acquiring better combinations of strength, ductility and toughness. This review describes the methodologies used to obtain this new kind of DI and the principal mechanical properties.